Identification and characterization of 4-[[4-(2-butynyloxy)phenyl]sulfonyl]-N-hydroxy-2,2-dimethyl-(3S)thiomorpholinecarboxamide (TMI-1), a novel dual tumor necrosis factor-alpha-converting enzyme/matrix metalloprotease inhibitor for the treatment of rheumatoid arthritis. - Zhang, Y; Xu, J; Levin, J; Hegen, M; Li, G; Robertshaw, H; Brennan, F; Cummons, T; Clarke, D; Vansell, N; Nickerson-Nutter, C; Barone, D; et al. (2004)
Tumor necrosis factor (TNF)-alpha is a well validated therapeutic target for the treatment of rheumatoid arthritis. TNF-alpha is initially synthesized as a 26-kDa membrane-bound form (pro-TNF) that is cleaved by a Zn-metalloprotease named TNF-alpha-converting enzyme (TACE) to generate the 17-kDa, soluble, mature TNF-alpha. TACE inhibitors that prevent the secretion of soluble TNF-alpha may be effective in treating rheumatoid arthritis (RA) patients. Using a structure-based design approach, we have identified a novel dual TACE/matrix metalloprotease (MMP) inhibitor 4-[[4-(2-butynyloxy)phenyl]sulfonyl]-N-hydroxy-2,2-dimethyl-(3S)thiomorpholinecarboxamide (TMI-1). This molecule inhibits TACE and several MMPs with nanomolar IC(50) values in vitro. In cell-based assays such as monocyte cell lines, human primary monocytes, and human whole blood, it inhibits lipopolysaccharide (LPS)-induced TNF-alpha secretion at submicromolar concentrations, whereas there is no effect on the TNF-alpha mRNA level as judged by RNase protection assay. The inhibition of LPS-induced TNF-alpha secretion is selective because TMI-1 has no effect on the secretion of other proinflammatory cytokines such as interleukin (IL)-1beta, IL-6, and IL-8. Importantly, TMI-1 potently inhibits TNF-alpha secretion by human synovium tissue explants of RA patients. In vivo, TMI-1 is highly effective in reducing clinical severity scores in mouse prophylactic collagen-induced arthritis (CIA) at 5, 10, and 20 mg/kg p.o. b.i.d. and therapeutic CIA model at 100 mg/kg p.o. b.i.d. In summary, TMI-1, a dual TACE/MMP inhibitor, represents a unique class of orally bioavailable small molecule TNF inhibitors that may be effective and beneficial for treating RA.